2001
DOI: 10.1111/j.1745-9125.2001.tb00941.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Law Violation and Depression: An Interactions Analysis*

Abstract: This paper integrates arguments from differential social control theory with sociological research on mental health to develop an interactionist explanation of the relationship between law violation and depression. We focus on the possibility that law violation and depression are related because they share common antecedents, as well as the possibility that these problems mutually influence one another over time. We test hypotheses derived from our theoretical perspective using covariance structure analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 72 publications
2
52
0
Order By: Relevance
“…Multivariate analyses provided similar results; after antisocial behavior such as use of street survival strategies was controlled, there was no statistically significant association between internalizing disorders and postrunaway arrest. As suggested by Coster and Heimer (2001), the significant bivariate associations may be because of common antecedents, such as abuse and neglect at home and use of street survival strategies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Multivariate analyses provided similar results; after antisocial behavior such as use of street survival strategies was controlled, there was no statistically significant association between internalizing disorders and postrunaway arrest. As suggested by Coster and Heimer (2001), the significant bivariate associations may be because of common antecedents, such as abuse and neglect at home and use of street survival strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Although past studies have found that major depression is highly associated with violent behavior and crime (Hodgins, 1993;Robins, 1993;Steadman et al, 1998;Stueve & Link, 1997), the precise nature of this relationship has not been explored. Individuals may try to alleviate depression by engaging in illegal acts (Agnew, 1992;Brezina, 1996Brezina, , 2000, or the association could be spurious since depression and law violation may have a common antecedent and result from a similar process (Coster & Heimer, 2001). In contrast, studies have indicated that other internalizing disorders, such as PTSD, are not associated with criminality.…”
Section: Mental Disorder Comorbidity and Criminalitymentioning
confidence: 99%
“…There is also the possibility that both of these unwanted outcomes can feed each other [23,29,30]. Adolescents with co-occurring depression and delinquent behaviors experience…”
Section: Causal Explanationmentioning
confidence: 99%
“…In Wolff and Ollendick's [13] review, three main explanations behind the link between depression and delinquency are worth mentioning regarding this problem: shared risk factors, the failure model, and the acting out model. Briefly, the shared risk model suggests that both problems have common sources that give rise to each separately, such as genetic effects [22] or social structural positions and stressful life events [23]. The failure model suggests that early delinquency results in negative social outcomes such as peer rejection or diminished social supports, which in turn result in depression [24].…”
Section: Causal Explanationmentioning
confidence: 99%
“…It is noteworthy that the attrition rate over this six-year-span was low (13%) and a comparison of respondents across the waves revealed that loss by demographic variables and delinquency did not compromise the representativeness of the sample. After conducting pairwise deletion of missing data, the final sample for their study included 1,550 subjects and their parents (De Coster & Heimer, 2001). …”
Section: Empirical Tests Of Dscmentioning
confidence: 99%